Temperature Of Cotton In The Stack During The Initial Storage Period (Texas Journal of Agriculture and Biological Sciences, 2025)
Since Uzbekistan gained independence, new equipment and technologies have been widely used in cotton production. Of course, we are well aware that significant financial costs lie behind these issues. Taking this into account, the President of our Republic and the Cabinet of Ministers are also paying great attention to equipping cotton gins with modern equipment and technologies that meet modern requirements, allocating the necessary funds from the republican budget.